Parental dependence on the nest's spatial cues in offspring recognition decreases with nestling growth in the azure-winged magpie. Issue 6 (8th April 2020) - Gao, Li-Fang; Zhang, Wen; Zhang, Hai-Yang; Zhu, Zhen-Qin; Zhang, Xiao-Dan; Du, Bo
Abstract: In altricial birds, to address which cues are used by parents to recognize their offspring, and when they switch between cues during reproduction, it has not been well determined. In this study, we address this question in a Tibetan population of the azure-winged magpie Cyanopica cyanus, by examining the dependence of parents on a nest's spatial position in offspring recognition. During the egg and nestling phases, azure-winged magpie nests were translocated to new positions across various distances from their original site, and parental responses to the translocated nests were investigated. Our findings show that a nest's spatial position is not connected with the survival of its young, but might be used as a cue in parental offspring recognition. When nests are translocated to a new position within a certain distance, parents could recognize their nests and returned to resume their parenting behaviors. Parental dependence on the nest's spatial position in offspring recognition is higher during the egg phase than during the nestling phase, and it decreases with the growth of nestlings. After nestlings reach a certain age, the nest' s spatial position was no longer used by parents as the single cue for offspring recognition. These findings suggest that azure-winged magpies switch their cues in offspring recognition during the different stages of reproduction. After parent–offspring communication has been established, the offspring's phenotypic traits may become a more reliable cue than the nest's spatial position in offspring recognition.